Leader-follower congruence in loneliness, LMX and turnover intention. Issue 4 (9th May 2016) - Chen, Yushuai; Wen, Zhonglin; Peng, Jian; Liu, Xiqin
Abstract : Purpose: – Research on workplace loneliness has thus far been dominated by perceptions of followers; hence, few researchers have considered the perspective of leader-follower congruence. The purpose of this paper is to examine how the leader-follower relationship mediates the relationship between leader-follower congruence/incongruence in workplace loneliness and turnover intentions. Design/methodology/approach: – Data were collected from 232 leader-follower dyads from ten companies in China. Polynomial regression combined with the response surface methodology was used to test the hypotheses. Findings: – Four conclusions were drawn. First, leader-member exchange (LMX) was higher when leaders and followers were aligned in terms of workplace loneliness than otherwise. Second, in the case of leader-follower congruence, LMX rose as their workplace loneliness fell. Third, in the case of incongruence, followers had lower LMX when they were lonelier than their leaders. Finally, LMX partially mediated the leader-follower congruence/incongruence effect of workplace loneliness on followers' turnover intention. Originality/value: – This study emphasized the importance of leaders' congruence with followers in workplace loneliness. Additionally, it extended research on leader-follower congruence from a positive perspective to a negative one.